Hospital Mortality in Acute Myocardial Infarction. Issue 5611 (20th July 1968) - Norris, R. M.; Bensley, K. E.; Caughey, D. E.; Scott, P. J.
Abstract : All 757 patients with acute myocardial infarction admitted to the three public hospitals in Auckland during one year were studied. About 7% died from cardiac arrhythmia four days or more after the onset of infarction. These patients had severe infarcts with circulatory failure on or shortly after admission to hospital. Late death from arrhythmia in patients recovering from circulatory failure may in many cases be preventable with anti-arrhythmic drugs.